(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The teaching of history in countries that have experienced colonisation has come under serious scrutiny at different times in their history. Worries about the contents of history programmes have been raised by politicians as well as educational technocrats who question the relevance of what is being taught as history to those on the classroom pews. In Cameroon, and particularly for the Anglophone subsystem of education, this debate is far from over despite the fact that the destiny of the country has rested in the hands of those who fought against colonialism for over fifty years now. This paper emanates from the premise that the colonial curriculum did not meet the realities of the new country since 1961. Consequently, there was a consensus of opinion that curriculum reform should focus on the teaching of local and national contents. By adopting the critical Decolonial perspective and living theory methodology the study focuses on history as one of those subjects which was used by the colonial authorities to entrench coloniality (Ndlovu-Gatsheni, 2013; Marsden, 2013; Rodney, 1982; Fanon, 1963) and was therefore in dire need of postcolonial reform. The study examines the extent to which this has been achieved in the Anglophone subsystem of Education by presenting what was learnt in the colonial history classroom in the British Southern Cameroons between 1916 and 1961. It then goes on to discuss the process of reform in the History curriculum of the Anglophone subsystem of education in Cameroon since independence.